Children's Character Education Through Various Learning Media In RA Normal Islamic Rakha - Hikmaturuwaida; Husin; Wati; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Early age is a golden age which is very effective in instilling various beneficial knowledge. The importance of character education in early childhood requires teachers to be creative and innovative in using learning media. Various learning media motivate children to learn. Not only forming a smart character but also being able to instill good values. This study aims to analyze various types of learning media in shaping the character of children in RA Normal Islam Rakha. This study used a qualitative method by taking the research location at RA Normal Islam Rakha. This type of research is descriptive research. Data collection was carried out using observation, documentation and interview methods. The results of the study show that teachers have a big role in children's character education. As role models as well as mentors in building children's character, teachers provide references or tools that can foster curiosity and not get bored in learning. The concept of playing while learning that children like is very effective when using a variety of learning media. The results of the research findings at RA Normal Islam Rakha carried out the formation of children's character through various learning media through educational toys and teaching aids.